The Principal’s Strategy for Implementing Merdeka Curriculum at SD Negeri 3 Margo Bhakti - Saronto, Saronto; Harapan, Edi; Kesumawati, Nila (Journal of Social Work and Science Education, 2025)
This study aims to analyze the principal’s strategies in planning, implementing, and evaluating Merdeka Curriculum and its contribution to improving the quality of education at SD Negeri 3 Margo Bhakti, Mesuji District, Ogan Komering Ilir Regency. As the first School leader (Sekolah Penggerak) in the area, SDN 3 Margo Bhakti has emerged as a pioneer and reference point in educational transformation, with the highest number of students among nearby elementary schools. A descriptive qualitative approach was employed to explore the leadership strategies adopted by the school principal in navigating the challenges and opportunities of Merdeka Curriculum implementation. The findings show that the principal’s strategy is organized into three main steps: planning, which uses SWOT analysis and matches the school’s goals; implementation, which focuses on teamwork among teachers, technology use, community participation, and clear budget management; and evaluation, which happens regularly through supervision and analysis of academic data. Merdeka Curriculum has greatly improved the quality of education at the school, making learning more flexible, enjoyable, and meaningful, while also promoting character development through the Pancasila Student Profile. Additionally, teachers receive ongoing training, mentoring, support from Merdeka Mengajar platform, and varied teaching methods. With strong leadership and steady execution, SDN 3 Margo Bhakti has successfully built an innovative, inclusive, and forward-looking learning environment.